(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Synthetic estrogens such as 17α-ethinylestradiol are among the most commonly found chemicals in surface and treated waters. Because it is a hormone, this compound has a high potential to act as an endocrine disruptor. The advanced oxidative processes (AOPs) are one of the techniques that have a good efficiency in the removal of these compounds, being the ones used in this work the photolysis, photocatalysis with titanium dioxide and the photocatalytic ozonation. To perform the experiment, a PVC tube reactor with a working volume of 4 L was prepared. Inside it, 2 ultraviolet lamps (UVC) of 15 w each were inserted. In a 2 L recirculation reservoir, connected to the tube, was installed a pump with a flow of 180 L.h-1 and ozone. The equipment was batch operated for 2 hours, the samples were collected every 10 min and analyzed in HPLC. In addition, a study was made of the influence of the variation of the catalyst concentration, on the removal efficiency. Photolysis presented efficiency of 87.6%, photocatalysis with TiO2 0.2 g.L-1 91.28% and photocatalytic ozonation 99.2%. The process did not show interference by adsorption of the hormone on the catalyst or the filter